PENERAPAN PENERANGAN JALAN UMUM (PJU) TENAGA SURYA DAN CCTV TERINTEGRASI IOT DI KELURAHAN PINANG TANGERANG - Imelda Simanjuntak; Fina Supegina; Trie Maya Kadarina; Triyanto Pangaribowo; Budi Yanto Husodo (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
A  Service (PKM) initiative led by lecturers and students from the Electrical Engineering Department at Mercu Buana University was conducted in Pinang Village, Tangerang City. The team successfully implemented solar-powered street lighting (PJU) and CCTV technology integrated with the Internet of Things (IoT). This program addressed security risks in poorly lit areas and reduced the high cost of conventional electricity for residents. The project was executed in the installation of eight independent (off-grid) solar-powered street lighting units and two cloud-based CCTV units. The lighting system utilizes a Passive Infrared (PIR) sensor with a 120° detection angle and a range of 6–8 meters. The lights operate automatically in economy mode at 30% power and switch to full brightness at 100% power upon motion detection, significantly conserving battery energy. The success of the program was(100% power) (30% power),reduc supported by the active participation of Pinang Village residents, who facilitated administration, community management, use of facilities, and outreach preparation. Final evaluation indicated a substantial positive impact, with residents' digital technology literacy increasing from a pre-test average of 42% to 90% in the post-test. The program eliminated vulnerable areas and provided neighborhood association (RT) administrators with real-time monitoring access via smartphone. Furthermore, this green technology innovation reduced the community's self-funded PLN electricity bill by up to 100% at the installation sites a safe, energy-independent, and sustainable residential environment.